Asset Management System through the design of a Jadex Agent System - Carbó, Javier; Molina, José M.; Patricio, Miguel A. (ADCAIJ: Advances in Distributed Computing and Artificial Intelligence Journal, 2016)
In this paper we have designed an agent system using JADEX platform in order to facilitate the asset management of an institution with several types of assets with some unknown similarities, and a high number of operators. Such environment would justify the use of a recommendation system that would provide an useful plan to be applied over an asset generated from previous maintenance operations hold over other assets. Here we provide the full design of such agent system, including the ontology, beliefs, plans, protocols and goals. This design has been implemented within GAIA: an information & asset management solution developed by Altran.